Usability Evaluation of E-Learning Website User Experience Using the TUXEL Method: A Technique for User Experience Evaluation in Learning Management System - Ilmananda, Asri Samsiar; Affandi, Arif Saivul (Journal of Multimedia Trend and Technology, 2025)
The purpose of this study was to determine the usability and User Experience (UX) on the E-Learning.net website with three aspects, namely general usability, pedagogical usability and user experience. This study uses the TUXEL method, a method used to evaluate usability and user experience in e-learning using three questionnaires, namely the problem reporting table, general LMS evaluation checklist and user experience evaluation. Data collection through validated questionnaires was then distributed to respondents by taking samples using non-probability sampling techniques. The sample used was obtained from a study of students at SMK N 12 Malang with a sample size of 10 students with characteristics of having knowledge about e-learning. The data obtained were analyzed using the descriptive analysis method. The evaluation results obtained from the three questionnaires, namely the problem reporting table, found 14 problems from the four variables, namely login, general interface, assignments and assessments. In the General LMS evaluation checklist, 18 problems were found from the four variables, namely Help and Documentation, LMS Learnability, Learning Through the LMS and LMS Flexibility. In the User Experience Evaluation, a positive mean value was obtained. The E-Learning website excels in the dimensions of support, innovation, creativity and motivation. E-Learning.net is suitable for use in independent learning.